Using ARDL Models To Study The Impact Of Internal Factors On Total Investments In The Syrian General Insurance Corporation (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aims to study and analyze the stationary of internal factors (the independent variables) represented by the following variables:1- liquidity ratio, 2- financial solvency,3- risk,4- number of branches, and also the stationary of the total investments variable (the dependent variable) in the Syrian General Insurance Corporation, using an autoregressive model for distributed lag periods.Study run equilibrium relationship between internal factors and the total investments variable in the Syrian General Insurance Corporation.Through this research, - it was concluded that both the variables of financial solvency and total investments were stationary at the original level, - the rest of the variables were stationary at the first difference,       - there was a long-run equilibrium relationship between internal factors and the total investments variable in the Syrian General Insurance Corporation.